Ultralow‐Power Piezo‐Optomechanically Tuning on CMOS‐Compatible Integrated Silicon‐Hafnium‐Oxide Platform (Laser Photonics Rev. 17(2)/2023). Issue 2 (11th February 2023) - Shen, Jian; Fan, Yuyan; Xu, Zihan; Wu, Liying; Wang, Ying; Li, Xiuyan; Gan, Xuetao; Zhang, Yong; Su, Yikai
Abstract : Photonic Integrated Circuits In article number 2200248, Yong Zhang, Xiuyan Li, Yikai Su, and colleagues experimentally demonstrate ultra‐low‐power piezo‐optomechanical tuning on a complementary metal‐oxide‐semiconductor (CMOS)‐compatible integrated silicon‐hafnium‐oxide platform. By introducing Zr‐doped HfO2 thin film as an active optical and piezoelectric layer, the tunable silicon‐hafnium‐oxide hybrid microring is capable of linear bidirectional tuning with ultra‐low power consumption. The hybrid silicon‐hafnium‐oxide technology with CMOS compatibility advances the field of ultra‐low‐power integrated photonic devices and can find applications in optical communications, computing, and spaces under cryogenic temperatures.